Holocentric chromosomes: from tolerance to fragmentation to colonization of the land - Zedek, František; Bureš, Petr (Annals of botany, 2018)
Background: The dispersed occurrence of holocentric chromosomes across eukaryotes implies they are adaptive, but the conditions under which they confer an advantage over monocentric chromosomes remain unclear. Due to their extended kinetochore and the attachment of spindle microtubules along their entire length, holocentric chromosomes tolerate fragmentation; hence, they may be advantageous in times of exposure to factors that cause chromosomal fragmentation (clastogens). Scope: It is shown that holocentric organisms may, indeed, thrive better than monocentric organisms under clastogenic conditions and that such conditions of various duration and intensity have occurred many times throughout the history of Earth's biota. One of the most important clastogenic events in eukaryotic history, in which holocentric chromosomes may have played the key role, was the colonization of land by plants and animals half a billion years ago. In addition to arguments supporting the anticlastogenic hypothesis of holocentric chromosomes and a discussion of its evolutionary consequences, experiments and analyses are proposed to explore this hypothesis in more depth. Conclusions: It is argued that the tolerance to clastogens explains the origin of holocentric lineages and may also have far-reaching consequences for eukaryotic evolution in general as exemplified by the potential role of holocentric chromosomes in terrestrialization.
Keywords: mutace; Animals; selekce (genetika); Chromosomes, Plant; Selection, Genetic; zvířata; biologická evoluce; Biological Evolution; Chromosomes; Mutation; chromozomy; chromozomy rostlin; centromera; Centromere; Eukaryota